Development of Hypercontent-Based Open-Ended Approach-Based Learning Devices to Improve SMK Students' Creative Thinking Abilities - Putri Elmaretha Purba; Elmanani Simamora; Izwita Dewi (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2023)
This study aims to: 1) obtain learning tools developed using an open-ended approach using hypercontent that meet validity, practicability, and effectiveness to improve students' creative thinking skills; and 2) describe how to apply learning tools developed using an open-ended approach using hypercontent to improve students' creative thinking skills. This study is concerned with development. The ADDIE development paradigm was used in this study. 1) The development of learning tools based on an open-ended approach using hypercontent meets the criteria of validity, practicability, and effectiveness of learning tools; 2) In trial I and trial II, the ability to improve creative thinking skills using learning tools based on an open-ended approach using hypercontent increased from 0.22 with low criteria to 0.39 with moderate criteria.